Characterization of phosphate solubilizing bacteria isolated from Pb contaminated soils and their potential for dissolving tricalcium phosphate - L E Susilowati; S Syekhfani (Brawijaya University, 2014)
Phosphorus solubilizing bacteria (PSB) enhances P availability in soils through dissolving inorganic P pools. The characteristics of PSB and the potential of three Pb tolerant phosphate solubilizing rhizobacteria, i.e. Pseudomonassp, Bacillus sp., and Actinomycites sp. were evaluated. PSB were isolated from soil samples contaminated with 300 and 500 mg Pb/kg after incubation for 30 days. Phosphate solubilizing bacteria were screened on for phosphate solubilisation ability in Pikovskaya agar medium (PA). In addition, two of the three indentified PSB strains (Pseudomonas sp. and Bacillus sp.) were characterized for their ability to solubilize tricalcium phosphate in Pikoskaya broth (PB) and also were examined their growth during culture medium incubation. The isolates exhibited different phosphate solubilization index, ranging from 1.87 to 2.98. Pseudomonas sp. had the highest ability to solubilize tricalcium phosphate: 9.82 mg P/ L and 12.23 mg P/ Lin Pikoskaya broth following the addition of 4 mg Pb/L and 2 mg /Pb L, respectively.